MENUMBUHKAN JIWA KEWIRAUSAHAAN BAGI SISWA SEKOLAH MENENGAH KEJURUAN - MUHAMMAD RAKIB; MARHAWATI NAJIB; MUHAMMAD TAUFIK (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
The problems experienced by SMK Negeri 1 Sidenreng Rappang currently are (1) the curriculum used is not in line with the competencies according to graduate users (link and match) so that it has not been able to meet the demands of the world of work, industry and business, (2) the quantity of graduates Unabsorbed in the business world and industry is quite high due to the low competence of graduates, incompatibility of competencies trained with the needs of the company/industry/business world and the lack of mental readiness to work graduates, (3) Lack of number and quality of productive teachers, (4) Lack of educational facilities and infrastructure, lack of competency test facilities and vocational certification facilities, and (5) Lack of cooperation between companies, government agencies, business and industry in the implementation of dual system education, namely the establishment of synergy between SMK and industry. The approach used in the application of science and technology is participatory (participatory learning) with an emphasis on the principle of learning by doing which is packaged through the stages of observation, testing, training, and evaluation. While the problem-based learning method is through lectures, discussions, questions and answers, and assignments (practice). The results achieved are (1) this community partnership program seen from the participation of partners can be categorized as very good, seen from the availability of a very adequate training place, the availability of learning tools or media such as computers, LCDs, and so on, and the selection of representative training participants from five the areas of expertise and activity of the trainees are categorized as very active, measured by the level of attendance, activeness in discussions, activeness in practice; (2) Overall training participants have understood the basic concepts and nature of entrepreneurship, Indonesia's future challenges, Indonesia's future in the hands of young people, and become entrepreneurs in the era of society 5.0, the success and failure factors of entrepreneurs, and business planning; and (3) the trainees have skills in making business plans.. ABSTRAKPermasalahan yang dialami oleh SMK Negeri 1 Sidenreng Rappang saat ini adalah (1) Kurikulum yang digunakan tidak selaras dengan kompetensi sesuai pengguna lulusan (link and match) sehingga belum mampu memenuhi tuntutan dunia kerja, dunia industri dan dunia usaha, (2) Kuantitas lulusan yang tidak terserap di dunia usaha dan dunia industri cukup tinggi disebabkan rendahnya kompetensi lulusan, ketidaksesuaian kompetensi yang dilatih dengan kebutuhan perusahaan/dunia industri/dunia usaha dan kurangnya kesiapan mental bekerja lulusan, (3) Kurangnya jumlah dan kualitas guru produktif, (4) Kurangnya fasilitas sarana dan prasarana pendidikan, kurangnya fasilitas uji kompetensi dan fasilitas sertifikasi SMK, dan (5) Kurangnya kerjasama perusahaan, lembaga pemerintah, dunia usaha dan dunia industri dalam pelaksanaan pendidikan sistem ganda yaitu terjalinnya sinergi antara SMK dan industri. Pendekatan yang digunakan dalam penerapan IPTEKS ini adalah partisipatif (participatory learning) dengan menekankan pada prinsip learning by doing yang dikemas melalui tahap observasi, testing, pelatihan, dan evaluasi. Sedangkan metode pembelajaran berbasis masalah melalui teknik ceramah, diskusi, tanya jawab, dan penugasan (praktik). Hasil yang dicapai adalah (1) program kemitraan masyarakat ini dilihat dari partisipasi mitra dapat dikategorikan sangat baik, dilihat dari tersedianya tempat pelatihan yang sangat memadai, tersedianya alat atau media pembelajaran seperti komputer, LCD, dan sebagainya, dan terpilihnya peserta pelatihana secara representatif dari lima bidang keahlian dan keaktifan peserta pelatihan dikategori sangat aktif diukur dari tingkat kehadiran, keaktifan dalam diskusi, keaktifan dalam praktik; (2) Peserta pelatihan secara keseluruhan telah memahami konsep dasar dan hakikat kewirausahaan, tantangan Indonesia masa depan, masa depan Indonesia di tangan anak muda, dan menjadi entrepreneur di era society 5.0, faktor keberhasilan dan kegagalan para wirausaha, dan perencanaan bisnis; dan (3) peserta pelatihan memiliki keterampilan dalam pembuatan perencanaan bisnis.